Model Pengaruh Dimensi Contract Change Order Terhadap Kinerja Proyek Konstruksi - Waluyo, Rudi; Angelica, Novelia Putri (Jurnal Civil Engineering Study, 2025)
Construction projects in their implementation have high uncertainty, which affects project performance. Contract change orders are one of the variables that influence construction project performance. This study aims to build a model and analyze the influence of CCO dimensions on construction project performance. This study uses survey and interview methods. The study was conducted in Palangka Raya City, Pulang Pisau Regency, and Katingan Regency, Central Kalimantan Province for two months, from February 10 to April 10, 2025. Questionnaires were distributed to 100 respondents who knew about CCO and construction project performance. There were 84 questionnaires that were considered complete and suitable for further analysis. Data analysis in this study used the structural equation modeling partial least squares (SEM-PLS) analysis method with the help of SmartPLS 4.0 software. The results showed that the dimensions of planning, administration, implementation, and stakeholders had a positive and significant influence on CCO. In addition, the CCO variable had a positive and significant influence on Project Performance. The CCO dimensions had a positive and significant influence on construction project performance.